Dampak Dana Alokasi Khusus Pertanian terhadap Ketahanan Pangan di Indonesia - Meliala, Eka; Djamaluddin, Sartika (Research and Development Agency Ministry of Home Affairs, 2024)
Indonesia's Food Security Index has decreased in the food availability category in 2022, influenced by food production. The government's efforts to achieve food security with DAK Non-Physical Food Security and Agriculture are a form of funds transfer to the regions. This study uses the robust fixed-effects panel data method to determine the effect of DAK Physical Agriculture and DAK Non-Physical Food Security and Agriculture on food security. The data used are secondary data from IKP and the realization of DAK Physical Agriculture and DAK Non-Physical Food Security and Agriculture from 2021 - 2023. The unit of analysis used is districts/cities in Indonesia. The dependent variable, the food security index, and the independent variable, DAK Food Security and Agriculture, are used to consider the factors of government spending, GRDP per capita, rice production, and population. The results of the analysis show that the Physical DAK has a significant influence on food security. At the same time, the Non-Physical DAK for Food Security and Agriculture is not significant for food security. The control variable of regional expenditure has a significant positive relationship with food security and population, which has a significant negative relationship with food security. The existence of a DAK Non-Physical Food Security and Agriculture budget that is too low and as a complementary fund causes not optimal outcomes from DAK Non-Physical Food Security and Agriculture. So, it is expected that in the future, there will be an increase in the portion of the allocation of DAK Non-Physical Food Security and Agriculture.